(untitled) (The Review of Diabetic Studies, 2024)
Background: The Kingdom of Saudi Arabia (KSA) is in the process of a radical healthcare transformation, as stipulated by the Saudi Vision 2030. With the risk of a constant shortage of nurses and the disastrously high turnover rates, the healthcare system is still struggling with the problem of the inherent nursing shortage and the intent to leave the job. The KSA has traditionally depended on the huge expatriate nurse workforce (around 60-70 percent), yet high turnover rates of migrants and Saudi nurses pose a risk to the quality of patient care and organizational sustainability. Purpose: The main aim of the systematic review is to summarize the current readings on the basic issues (push factors) that cause nursing turnover in Saudi Arabia and to appraise the efficacy of various retention measures (pull factors) used to stabilize the staff. Methods: The systematic review was done according to PRISMA (Preferred Reporting Items to Systematic Reviews and Meta-Analyses) principles. An extensive electronic search was carried out in electronic databases such as PubMed, CINAHL, Scopus, and Google Scholar of peer-reviewed articles published between 2016 and 2026. The studies were considered as including those that used quantitative, qualitative, or mixed-methods research designs to explore the topic of nursing retention or turnover specifically in the Saudi Arabian setting. The data of the chosen studies were collected, quality-assessed, and synthesized by means of the thematic analysis. Conclusion: Saudi Arabia should move the recruitment-intensive system towards a retention-oriented approach to achieve Vision 2030. The key to success is balancing the organizational policies with the cultural beliefs of locals and the local workforce and the ability to create an inclusive and accommodating atmosphere to the expatriate workers. Leadership development and work-life balance programs should be given priority to policy makers to have a strong and dedicated workforce in the nursing profession.